Al-Tadābīr al-Sharʿiyyah wa-al-Qānūniyyah li al-Ḥadd min Ẓāhirat Ḥirmān al-Nisāʾ min al-Mīrāth fī Lībiyā - Isniba, Abdallah Al-Sharif Ahmed Asneiba; Azbeyda, Hamed Abdel Salam Mansour (Yayasan Pesantren Mahasiswa An-Nur, 2024)
The topic of this study revolves around the phenomenon of depriving women of inheritance in Libyan society, elucidating the legal and Islamic perspectives on this issue. The aim is to identify its causes and effects and to determine the most important legal and Sharia-based measures to mitigate it. This study employs a descriptive method to understand this phenomenon and identify its causes, as well as a comparative method by examining the provisions of Islamic Sharia related to the topic and comparing them with relevant articles of Libyan law. The study reached several key conclusions, the most important of which is: that the Libyan criminal legislator has stipulated that the inheritance of women and the determination of their shares should be by Islamic Sharia. Additionally, the weakening of religious motivation and ignorance of the seriousness of committing this crime are among the main reasons leading to the deprivation of women from their inheritance. The violation of women's inheritance rights falls under sins that have no fixed punishment or atonement, and this sin, proven by the text of the Quran and the Sunnah of the Prophet, requires punishment according to Sharia and legal texts.